2010
DOI: 10.5039/agraria.v5i1a591
|View full text |Cite
|
Sign up to set email alerts
|

Adubação mineral no crescimento e composição mineral da palma forrageira –Clone IPA-201

Abstract: A pesquisa foi realizada na casa de vegetação do Instituto Agronômico de Pernambuco-IPA, Recife-PE, objetivando avaliar os efeitos dos níveis de fósforo (P) e potássio (K) no crescimento e composição química da palma forrageira clone IPA-20. Estudou-se quatro níveis de P (0; 200; 400 e 800 kg P 2 O 5 ha-1) e quatro níveis de K (0; 200; 400 e 800 kg de K 2 O ha-1), em um arranjo fatorial 4 x 4, num delineamento de blocos casualizados, com quatro repetições. As observações foram realizadas em intervalos de 28 di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
13

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 5 publications
1
21
0
13
Order By: Relevance
“…Balance of micronutrients (boron, copper, iron, manganese, sodium and zinc) as a function of the extraction/ export by cactus pear and the amount added to the soil through NPK fertilization 620 days after planting of extraction/export: Mn, Zn, Fe, Na, B and Cu. Similar relationships for micronutrients were reported by Silva et al (2012) andDubeux Júnior et al (2010).…”
Section: Extraction/export Of Micronutrients X Supplysupporting
confidence: 90%
“…Balance of micronutrients (boron, copper, iron, manganese, sodium and zinc) as a function of the extraction/ export by cactus pear and the amount added to the soil through NPK fertilization 620 days after planting of extraction/export: Mn, Zn, Fe, Na, B and Cu. Similar relationships for micronutrients were reported by Silva et al (2012) andDubeux Júnior et al (2010).…”
Section: Extraction/export Of Micronutrients X Supplysupporting
confidence: 90%
“…According to Dubeux Júnior et al (2010), the increase in P fertilization leads to greater absorption and accumulation in the dry matter of cactus forage. Dubeux Júnior et al (2006) found low responses to P in the production of 'Gigante' cactus forage and positive responses only when the contents of P available in the soil were lower than 10 mg kg -1 .…”
Section: Resultsmentioning
confidence: 99%
“…The treatment with longest irrigation fertigation interval and treated with domestic sewage led to higher Mg absorption by the plant (Figure 5) (DUBEUX JÚNIOR et al, 2010). Thus, if there is no replenishment of nutrients through fertilization, there will be a reduction in the yield and quality of the forage.…”
Section: Magnesium Concentration In Cladodesmentioning
confidence: 99%